Additions to the Tanaidacea (Crustacea: Peracarida) of Rangitâhua, the Kermadec Islands, from the Southwest Pacific Expedition 2017 - Bird, Graham J. (Zootaxa, 2020)
Four new species or morphospecies of tanaidaceans, all of small size (c. 1 mm), from the Rangitâhua-Kermadecs component of the Southwest Pacific Expedition 2017 survey are recorded and described: Collettea coralensis n. sp., leptocheliid sp.RK#1, Psalidichelia concinna n. g. & n. sp., and Stachyops cf. sebparri. Six had been described or recorded from the earlier Kermadec Biodiscovery Expedition 2011: Aparatanais tetradonta, Chondrochelia acrolophus, Metatanais progenitor, Paradoxapseudes floppae, Tanais sp., and Zeuxo kermadecensis. This brings the number of known tanaid species from the Rangitâhua/Kermadecs group to ten. The records of the Collettea species are notable for the shallow depths from which they were collected, 4–18 m, and the habitats sampled: coral rubble, coral encrusts on rocks, and red algae.